2004
DOI: 10.1016/j.mod.2004.04.010
|View full text |Cite
|
Sign up to set email alerts
|

FGF2 triggers iris-derived lens regeneration in newt eye

Abstract: Lens regeneration in newts occurs exclusively from the dorsal aspect of the iris pigment epithelium. Although the phenomenon has been a paradigm of experimental tissue regeneration, little is understood about how it is initiated and restricted to the dorsal iris. Here we show among various growth factors injected in an intact eye, a single injection of FGF2 specifically caused morphological changes of the iris characteristic of lens regeneration, induced expression of transcription factor genes Pax6, Sox2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 29 publications
2
83
0
Order By: Relevance
“…While this possibility is under investigation, it has already been demonstrated that primate ES cells can be directed to form Pax6-and ␣A-crystallin-expressing lentoid bodies after treatment with FGF2 (Ooto et al, 2003). FGF2 triggers lens regeneration in newt (Hayashi et al, 2004), and FGF molecules and their receptors are known to play a role in different aspects of lens formation (for…”
Section: Ectopic Lens Formationmentioning
confidence: 99%
“…While this possibility is under investigation, it has already been demonstrated that primate ES cells can be directed to form Pax6-and ␣A-crystallin-expressing lentoid bodies after treatment with FGF2 (Ooto et al, 2003). FGF2 triggers lens regeneration in newt (Hayashi et al, 2004), and FGF molecules and their receptors are known to play a role in different aspects of lens formation (for…”
Section: Ectopic Lens Formationmentioning
confidence: 99%
“…However, the continued expression of genes involved in embryonic lens induction in the adult newt suggests that some genes may be involved in both processes. Indeed, lens differentiation-controlling genes such as FGFs, Pax-6, Sox-2, MafB, and Prox-1 have been found in both dorsal and ventral irises of intact as well as regenerating newt eyes (10)(11)(12)(13)(14). Even though it has been established that the Pax-6 gene is expressed during the process of lens regeneration, a direct association with events of regeneration has never been established (10,13,14).…”
mentioning
confidence: 99%
“…Hayashi and colleagues have shown that intraocular injection of recombinant FGF2 can trigger lens regeneration from the dorsal iris without previously removing the host lens. Injection of FGF2 also induced expression of several transcription factors such as Pax6, Sox2, and MafB [19]. Intraocular injections of recombinant newt FGF1 also had effects on newt lens regeneration [20].…”
Section: Fgf Signaling Pathwaymentioning
confidence: 97%
“…However, transfection of FGFR-1 into cultured newt iris PECs (dorsal and ventral) with subsequent re-implantation into host newts did not induce lens regeneration from the ventral iris (0/11 -0%) and had no observable effect on lens regeneration from the dorsal iris (2/7 -29%) (Tsonis lab; unpublished) suggesting that FGFR-1 signaling is not sufficient for lens regeneration. To confirm that FGF activity is essential to lens regeneration, Hayashi and others also injected soluble FGF receptors to compete with endogenous receptors for FGF binding [19]. It was observed during FGFR2 (IIIc)/Fc (binding FGF 1,2,4, and 9) daily injections that lens regeneration was completely inhibited.…”
Section: Fgf Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation